A Holistic Approach to Understanding the Desorption of Phosphorus in Soils - Menezes-Blackburn, Daniel; Zhang, Hao; Stutter, Marc; Giles, Courtney D; Darch, Tegan; George, Timothy S; Shand, Charles; Lumsdon, David; Blackwell, Martin; Wearing, Catherine; Cooper, Patricia; Wendler, Renate; et al. (Environmental science & technology, 2016)
The mobility and resupply of inorganic phosphorus (P) from the solid phase were studied in 32 soils from the UK. The combined use of diffusive gradients in thin films (DGT), diffusive equilibration in thin films (DET) and the “DGT-induced fluxes in sediments” model (DIFS) were adapted to explore the basic principles of solid-to-solution P desorption kinetics in previously unattainable detail. On average across soil types, the response time (T c) was 3.6 h, the desorption rate constant (k–1) was 0.0046 h–1, and the desorption rate was 4.71 nmol l–1 s–1. While the relative DGT-induced inorganic P flux responses in the first hour is mainly a function of soil water retention and % Corg, at longer times it is a function of the P resupply from the soil solid phase. Desorption rates and resupply from solid phase were fundamentally influenced by P status as reflected by their high correlation with P concentration in FeO strips, Olsen, NaOH–EDTA and water extracts. Soil pH and particle size distribution showed no significant correlation with the evaluated mobility and resupply parameters. The DGT and DET techniques, along with the DIFS model, were considered accurate and practical tools for studying parameters related to soil P desorption kinetics.